2014
DOI: 10.4238/2014.october.31.25
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellite loci for Bixa orellana, an important source of natural dyes

Abstract: ABSTRACT. Annatto (Bixa orellana) is a plant native from the American continental tropical zone. The seeds are used to produce a carotenoid-based yellow to orange food coloring. Microsatellite markers were developed for the Brazilian native species Bixa orellana to describe its genetic diversity and structure as well as to support conservation studies. Twenty-five microsatellite loci were isolated and characterized using an enriched genomic library. Ten loci were polymorphic in the 50 accessions sampled in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…As a result, local inbreeding coefficients were high in all populations (Table 2). Similar results for cultivated accessions were reported by Dequigiovanni et al (2014) Higher levels of genetic diversity in wild than cultivated crops were also found in other crops, due to genetic bottleneck effects during domestication, such as in tepary beans (Phaseolus acutifolius) (Blair et al 2012, Gujaria-Verma et al 2016 (Bitocchi et al 2013), apricot (Prunus armeniaca) (Bourguiba et al 2012), and sunflower (Helianthus annuus) (Mandel et al 2011). However, this is not always the case, since in some crops, e.g., in carrot (Daucus carota subsp.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…As a result, local inbreeding coefficients were high in all populations (Table 2). Similar results for cultivated accessions were reported by Dequigiovanni et al (2014) Higher levels of genetic diversity in wild than cultivated crops were also found in other crops, due to genetic bottleneck effects during domestication, such as in tepary beans (Phaseolus acutifolius) (Blair et al 2012, Gujaria-Verma et al 2016 (Bitocchi et al 2013), apricot (Prunus armeniaca) (Bourguiba et al 2012), and sunflower (Helianthus annuus) (Mandel et al 2011). However, this is not always the case, since in some crops, e.g., in carrot (Daucus carota subsp.…”
Section: Resultssupporting
confidence: 61%
“…Deviations from HWE may occur because B. orellana has a mixed mating system and can tolerate both autogamy and allogamy (Rivera-Madrid et al 2006, Valdez-Ojeda et al 2010, Joseph et al 2012)changes in botanical composition could cause variable (unstable. Similarly, Dequigiovanni et al (2014) found deviations from HWE in eight out of ten loci analyzed. No significant linkage disequilibrium was detected for any pair of loci tested after Bonferroni correction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen SSR markers developed for B . orellana [ 17 , 23 ] were used in this study ( Table 2 ; S1 Table ). Three fluorescent dyes (NED, FAM and HEX) were attached to the 5' end of the M13 universal primer sequence ( ) following Schuelke [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, SSR markers are important tools to assess genetic diversity and genetic structure of populations, especially for wild species [ 14 ]. There are very few genetic studies in annatto [ 15 17 ] and no studies have yet evaluated population structure and genetic diversity of wild populations of annatto ( B . orellana var.…”
Section: Introductionmentioning
confidence: 99%